Problem of effective implementation of corporate information systems in nowadays economy - T. Godina; A. Terekhova (Вестник университета)
The paper considers the most essential characteristics and specifics of corporate information systems development. Authors bring forward the most common problems and reasons of deployment fails, considering its impact of project effectiveness through their own experience of such deployments.